Electrocoating copper foil having uniform mat surface
Patent Information
- Application Number
- JP2024144047
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-25
- Filing Date
- 2024-08-26
- Publication Date
- 2025-03-07
Smart Images

Figure 2025031701000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrodeposited thick copper foil having a uniform matte surface. The present invention also relates to a method for producing the electrodeposited copper foil of the present invention and to articles produced therefrom. [Background technology]
[0002] Electronic systems used in vehicles include engine management systems, ignition systems, car computers, telematics, in-car entertainment systems, etc. Electronic systems are becoming an increasingly large part of the cost of a car. As a result, the demand for automotive PCBs used in the above mentioned electronic systems is increasing significantly.
[0003] Compared with traditional consumer electronics, automotive PCBs must meet high reliability and safety standards. More specifically, copper foil suitable for use in automotive PCBs must have three characteristics: (1) be thick enough to withstand high working current and have good heat dissipation; (2) have a uniform matte surface to avoid poor etching during the manufacturing process and / or short circuit occurrence under working conditions; and (3) be capable of being manufactured at industrial production speeds.
[0004] The thickness of electrodeposited copper foil (hereinafter abbreviated as ED copper foil) is proportional to the electrodeposition time at a certain current density. Obtaining thicker ED copper foil without reducing the production speed requires a higher current density (i.e. 30A / dm 2This can be achieved by electrodeposition at current densities of 1000 kV or more (>1000 kV). However, the uniformity of the matte surface of the copper foil generally decreases with increasing current density. At high current densities, copper crystals may deposit non-uniformly at certain locations, forming abnormal protrusions (exceptional height and size) on the deposition surface of the ED copper foil, resulting in poor surface uniformity. Figure 1A shows an SEM image of an ED copper foil with abnormal protrusions among multiple protrusions on the matte surface. In contrast, Figure 1B shows an SEM image of an ED copper foil with a uniform matte surface containing numerous protrusions of similar height and size. The uniform surface of ED copper foil as shown in Figure 1B is desired for applications in automotive PCBs.
[0005] Generally, when the thickness of the copper foil is less than 30 μm, applying a high current density during electrodeposition will not cause serious uniformity problems on the matte side (i.e., the deposit side) of the ED copper foil because the electrodeposition time is relatively short and there is not enough time for abnormal protrusions to grow. However, if the electrodeposition time is extended to produce a thick copper foil, it is expected that many abnormal protrusions will form on the matte side of the ED foil. As a result, PCBs produced from thick copper foils with poor uniformity are prone to insufficient etching during the circuit formation stage, which may cause short circuit problems during subsequent operations.
[0006] Known solutions to minimize the formation of the above-mentioned abnormal protrusions on the matte side of ED copper foil include (1) reducing the current density used for electrodeposition; and (2) adding large amounts of traditional additives to the electrolyte. The main drawback of the first solution is that the production rate of the copper foil decreases as the current density decreases. In addition, the first solution can suppress the size and number of abnormal protrusions, but cannot stop the formation of abnormal protrusions.
[0007] The second solution is to add conventional additives to obtain a uniform copper foil surface under high current density conditions. However, the presence of a large amount of conventional additives in the electrodeposition cell shortens the service life of the electrolyte and requires an extra removal step when disposing of the electrolyte as waste. In addition, it is difficult to control the quality of the copper foil during the continuous production process, i.e., by refilling the electrodeposition cell with a large amount of conventional additives with new electrolyte.
[0008] Considering the above, there is a need to develop electrodeposited copper foil with a uniform matte surface to benefit the printed circuit board industry as a whole, especially automotive PCBs. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] U.S. Pat. No. 8,268,158 [Patent Document 2] U.S. Pat. No. 7,662,981 [Patent Document 3] U.S. Patent No. 7,374,652 [Patent Document 4] U.S. Patent No. 6,800,188 Summary of the Invention [Means for solving the problem]
[0010] In order to solve the above problems, the present invention provides an electrodeposited copper foil having a uniform matte surface and a method for manufacturing the electrodeposited copper foil.
[0011] According to a first aspect of the present invention, an electrodeposited copper foil having a uniform matte surface is provided.
[0012] The electrodeposited copper foil has an average thickness (T Ave The electroplated copper foil has a matte surface and a shiny surface; the matte surface of the copper foil includes a plurality of protrusions; and after polishing, the matte surface is 1 mm thick.2 50μm per 2 The number of protrusions on the mat surface with a flattened top having a surface area of more than 50+ ) is 8.0 or less; the average thickness is measured by scanning electron microscopy (SEM); the tops of a plurality of protrusions on the matte side are flattened by a) placing the electrodeposited copper foil on a glass substrate such that the matte side is in contact with the glass substrate, and b) polishing the shiny side of the electrodeposited copper foil to about 1 μm using 1200 grit silicon carbide sandpaper; and the number and surface area of protrusions on the matte side having flattened tops after polishing are counted and measured using an optical microscope having a magnification of 50 times or more and a resolution of at least 0.1 μm.
[0013] According to a second aspect of the present invention, there is provided a method for producing the above-mentioned electrodeposited copper foil, the method comprising the steps of: i) providing an electrolyte in an electrolytic cell; ii) applying a current at a certain current density to an anode plate and a rotating cathode electrode drum spaced apart in an electrolyte; iii) electrodepositing copper foil onto a rotating cathode drum; and iv) Peeling off the copper foil formed in step iii) to obtain an electrodeposited copper foil. Including, The electrodeposited copper foil has an average thickness of about 30 μm to about 400 μm; The electrodeposition in step iii) is about 30 A / dm 2 ~ approx. 100A / dm 2 at a current density of; The electrolyte is Copper sulfate from about 120 g / L to about 450 g / L; Sulfuric acid from about 30 g / L to about 140 g / L; about 0.1 ppm to about 60 ppm chloride ions; and Additives from about 0.1 ppm to about 50 ppm Includes.
[0014] According to a third aspect of the present invention, a surface treated electrodeposited copper foil comprises or is made from the electrodeposited copper foil of the present invention.
[0015] According to a fourth aspect of the present invention, there is provided an article comprising or made from the electrodeposited copper foil of the present invention.
[0016] In one embodiment, the article includes a negative current collector for a lithium ion battery, a copper clad laminate, a flexible copper clad laminate, a heat sink, or a printed circuit board. [Brief description of the drawings]
[0017] [Figure 1] SEM images of two copper foil specimens are shown. Figure 1A shows the matte side of the copper foil specimen of Comparative Example 3 (CE3) which had abnormal protrusions. Figure 1B shows the matte side of the copper foil specimen of Example 9 (E9) which had no abnormal protrusions and was highly uniform. [Diagram 2] 1 is a cross-sectional view of two surface treated electrodeposited copper foils according to an embodiment of the present invention. [Diagram 3] 3 shows SEM photographs of the cross-sections of two copper foil specimens: Figure 3A is a photograph of a copper foil specimen of Comparative Example 3 (CE3) and Figure 3B is a photograph of a copper foil specimen of Example 9 (E9). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] All publications, patent applications, patents, and other references mentioned herein are expressly incorporated by reference herein in their entirety for all purposes as if fully set forth, unless otherwise noted.
[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. In case of conflicts, the present specification, including definitions, will control.
[0020] Unless otherwise stated, all percentages, parts, ratios, etc. are by weight.
[0021] As used herein, the term "produced from" is synonymous with "comprising." As used herein, the terms "comprise," "including," "including," "including," "having," "having," "containing," or "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or device that includes a list of elements is not necessarily limited to only those elements and may include other elements not expressly listed or inherent to such composition, process, method, article, or device.
[0022] The transitional phrase "consisting of" excludes any element, step, or ingredient not specified. When in a claim, such a phrase would exclude the inclusion of materials other than those recited, except for impurities ordinarily associated with them. When the phrase "consisting of" appears in a clause in the body of a claim, rather than immediately following a preamble, it limits only the elements specified in that clause; other elements are not excluded from the claim as a whole.
[0023] The transitional phrase "consisting essentially of" is used to define a composition, method, or apparatus that includes materials, steps, features, components, or elements in addition to those literally contemplated, provided that these additional materials, steps, features, components, or elements do not materially affect the basic and novel characteristics of the claimed invention. The term "consisting essentially of" occupies the intermediate region between "comprising" and "consisting of."
[0024] The term "comprising" is intended to include embodiments encompassed by the terms "consisting essentially of" and "consisting of." Similarly, the term "consisting essentially of" is intended to include embodiments encompassed by the term "consisting of."
[0025] When an amount, concentration, or other value or parameter is given as either a range, a preferred range, or a list of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed from any pairing of any upper range limit or preferred value with any lower range limit or preferred value, whether or not the ranges are separately disclosed. For example, if a range of "1 to 5" is recited, the recited range should be interpreted as including the ranges "1 to 4," "1 to 3," "1 to 2," "1 to 2 and 4 to 5," "1 to 3 and 5," etc. When a range of numerical values is recited herein, unless otherwise specified, the range is intended to include the endpoints thereof, as well as all integers and fractions within the range.
[0026] When the term "about" is used to describe a value or an endpoint of a range, the disclosure should be understood to include the specific value or endpoint referred to.
[0027] Furthermore, unless expressly stated to the contrary, "or" means an inclusive "or" and not an exclusive "or." For example, a condition A "or" B is satisfied by any one of the following: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and A and B are both true (or exist).
[0028] As used herein, the term "hydrocarbon group" refers to an organic compound having at least one carbon atom and at least one hydrogen atom, optionally substituted with one or more substituents as indicated. An "alkyl group" refers to a monovalent straight or branched chain saturated hydrocarbon having a specific number of carbon atoms, such as methyl, ethyl, n-propyl, i-propyl, or the different butyl, pentenyl, and hexenyl isomers. An "alkylene group" refers to a divalent alkyl group. A "cycloalkyl group" refers to a monovalent group having one or more saturated rings in which all ring members are carbon, such as cyclopropyl, cyclobutyl, cyclopentyl, and cyclohexyl; a "cycloalkylene group" refers to a divalent cycloalkyl group. Examples of "cycloalkylene" include cyclopropylene, cyclobutylene, cyclopentylene, and cyclohexylene. An "aryl group" refers to a monovalent aromatic monocyclic or polycyclic ring system that may include groups whose ring members are composed of carbon atoms and have an aromatic ring fused to at least one cycloalkyl or heterocycloalkyl ring, such as phenyl, biphenyl, triphenyl, naphthyl, and binaphthyl. An "arylene group" refers to a divalent aryl group. The total number of carbon atoms in a substituent is indicated by the prefix "Ci-Cj."
[0029] The term "optionally substituted" is used interchangeably with the terms "substituted or unsubstituted" or "(un)substituted." The phrase "optionally substituted with 1 to 4 substituents" means that there are no substituents (i.e., unsubstituted) or there are 1, 2, 3, or 4 substituents (limited by available bonding positions). Unless otherwise indicated, an optionally substituted group can have one substituent at each substitutable position of the group, and each substituent is independently selected. "Halide" refers to fluoride, chloride, bromide, and iodide.
[0030] The embodiments of the invention described in the Summary of the Invention may be combined in any manner, including any other embodiment described herein, and the descriptions of variables in the embodiments relate not only to the composite laminate of the invention, but also to articles made therefrom.
[0031] The invention is described in detail herein below.
[0032] The present invention relates to an electrodeposited copper foil with a uniform matte side. Electrodeposited (ED) copper foil is manufactured by electrodeposition. Each ED copper foil has two surfaces, the surface that faces the electrolyte during the manufacturing process is called the "deposition side" and the opposite surface that contacts the cathode drum / roller is called the "drum side" or "roller side". Both surfaces of ED copper foil have a distinct appearance, so the plated side is also called the matte side and the drum side is called the shiny side. The matte side of ED copper foil contains multiple protrusions when viewed under a high magnification microscope. Due to non-uniform copper deposition, some protrusions are abnormally tall and larger than other protrusions. Typically, the uniformity of the matte side of ED copper foil can be affected by the number and size of the abnormally tall and large protrusions per unit area of the copper foil. As mentioned above, non-uniform copper deposition can cause a large number of protrusions, such as a large number of protrusions, at a current of about 30 A / dm. 2 This phenomenon is particularly noticeable when electrodeposition is performed at high current densities such as those mentioned above. For this reason, it is known that ED copper foils manufactured at high current densities as in the past have insufficient uniformity on the matte surface.
[0033] The abnormally tall and large protrusions on the matte side of the ED copper foil can be revealed by a) placing the electrodeposited copper foil on a glass substrate so that the matte side is in contact with the glass substrate, and b) polishing the shiny side of the electrodeposited copper foil approximately 1 μm using 1200 grit silicon carbide sandpaper. The tops of the abnormally tall and large protrusions are then flattened.
[0034] The surface area of each protrusion with a flattened top after polishing as described above can be observed and measured by scanning electron microscopy (SEM). For example, FIG. 1A shows an SEM photograph of an ED copper foil specimen produced by electrodeposition in an electrolyte containing a conventional additive (i.e., CE3), in which the matte surface of the ED copper foil specimen contains multiple protrusions. Among these protrusions, there is one abnormally tall and large protrusion with a flattened surface after polishing.
[0035] Typically, the surface area is 50 μm2 with a flat top after polishing. 2 Abnormally high and large protrusions, greater than or equal to 50μm2 in surface area, with a flat top after polishing, are counted as they significantly affect the uniformity of the matte surface of the ED copper foil. 2 An optical microscope with a magnification of 50 times or more and a resolution of at least 0.1 μm is used to observe and count the number of protrusions that are equal to or greater than PA. 50+ The size of the observation window of an optical microscope may vary depending on the device, so the matte surface is expressed as 1 mm 2 Number of above projections per unit (PA 50+ ) is used as an index of the uniformity of the matte surface of ED copper foil.
[0036] Furthermore, the uniformity of the matte side of ED copper foil can be characterized by the uniformity factor (UF), which is calculated by Equation 1: UF=A max / T Ave (Formula 1) (In the formula, A max : the maximum surface area of the protrusions on the matte surface with flattened tops after polishing; and T Ave : Average thickness of ED copper foil (T Ave )).
[0037] The electrodeposited copper foil of the present invention having a uniform matte surface has the following characteristics: (1) an average thickness (T Ave (2) 8.0 or less, matte surface 1 mm 2 Around PA 50+ Having.
[0038] The electrodeposited copper foil of the present invention further has a fourth characteristic in that the matte side of the electrodeposited copper foil has a uniformity factor (UF) of 5.5 μm or less.
[0039] In some embodiments of the present invention, the matte surface is 1 mm 2 Around PA 50+ is about 7.0 or less, about 6.0 or less, about 5.0 or less, or about 4.0 or less, 3.0 or less, or about 2.0 or less.
[0040] In some embodiments of the present invention, the matte side of the electrodeposited copper foil has a UF of 4.5 μm or less, or 3.5 μm or less, or 2.5 μm or less.
[0041] A second aspect of the present invention is i) providing an electrolyte into an electrolytic cell; ii) applying a current at a current density to an anode plate and a rotating cathode drum spaced apart in an electrolyte; iii) electrodepositing copper foil onto a rotating cathode drum; and iv) A step of peeling off the copper foil formed in step iii) to obtain an electrodeposited copper foil. A method for producing the above-mentioned electrodeposited copper foil having a uniform matte surface, comprising: The electrodeposited copper foil has an average thickness of about 30 μm to about 400 μm; The electrodeposition in step iii) is about 30 A / dm 2 ~ approx. 100A / dm 2 at a current density of; The electrolyte is Copper sulfate from about 120 g / L to about 450 g / L; Sulfuric acid from about 30 g / L to about 140 g / L; about 0.1 ppm to about 60 ppm chloride ions; and Additives from about 0.1 ppm to about 50 ppm The present invention provides a method comprising:
[0042] In the method of the present invention, the electrolyte comprises copper sulfate, sulfuric acid, chloride ions, and additives. Copper sulfate is the source of copper ions and sulfuric acid is the electrolyte in the electrolyte. Both copper sulfate and sulfuric acid are commercially available from a variety of sources and are used without further purification.
[0043] In some embodiments of the invention, the amount of copper sulfate in the electrolyte is from about 120 g / L to about 450 g / L; or from about 180 g / L to about 400 g / L; or from about 240 g / L to about 350 g / L, based on the total volume of the electrolyte.
[0044] In some embodiments of the present invention, the amount of sulfuric acid in the electrolyte is from about 30 g / L to about 140 g / L; or from about 35 g / L to about 130 g / L; or from about 40 g / L to about 120 g / L, based on the total volume of the electrolyte.
[0045] The source of chloride ions may be copper chloride or hydrochloric acid. These sources of chloride ions are commercially available and are used without further purification.
[0046] In some embodiments of the present invention, the amount of chloride ions in the electrolyte is from about 0.1 ppm to about 60.0 ppm, or from about 1.0 ppm to about 55.0 ppm, or from about 2.5 ppm to about 50.0 ppm, or from about 5.0 ppm to about 45.0 ppm, or from about 10.0 ppm to about 40.0 ppm, based on the total weight of the electrolyte.
[0047] The additives used in the present invention are not particularly limited, so long as the electrodeposited copper foil produced by the method of the present invention has a uniform matte surface. Additives suitable for use in the electrolyte include gelatin, glue, cellulose, organic sulfonic acid or its salt, nitrogen-containing cationic polymer, or mixtures thereof. Depending on the specific application of the ED copper foil, other additives such as accelerators, inhibitors, leveling agents, or crystal orientation adjusters may also be added in combination of one or more.
[0048] In some embodiments of the present invention, the additive comprises gelatin, glue, cellulose, an organic sulfonic acid or its salt, a nitrogen-containing cationic polymer, or a mixture thereof.
[0049] In the method of producing electrodeposited copper foil of the present invention, the amount of additive in the electrolyte depends on the particular additive selected, the concentration of copper ions, the concentration of sulfuric acid in the electrolyte, and the current density applied.
[0050] In the practice of mass production of copper foil, the electrolyte is usually continuously recycled by replenishing necessary components (e.g., copper ions, sulfuric acid, chloride ions, etc.), and is filtered through a filter material to remove impurities and decomposed additives before pumping to the electrolytic cell. If the total amount of additives is 50 ppm or less based on the total weight of the electrolyte, this is beneficial for reducing the use of filter materials such as activated carbon. Therefore, the manufacturing method of the electrodeposited copper foil of the present invention is beneficial for mass production and environmental protection.
[0051] In one embodiment of the present invention, the total amount of additives in the electrolytic solution is from about 0.1 ppm to about 50.0 ppm, or from about 0.5 ppm to about 40.0 ppm, or from about 1.0 ppm to about 30.0 ppm.
[0052] Known organic sulfonic acids or salts thereof suitable for use as brighteners or accelerators in the electrolyte include bis(sodium sulfopropyl) disulfide (SPS), sodium 3-(benzthiazolyl-2-mercapto)-1-propanesulfonate (ZPS), 3-S-thiuronium propanesulfonate (UPS), sodium 3-mercapo-1-propanesulfonate (MPS), etc. The amount of organic sulfonic acid or salt thereof in the electrolyte is typically in the range of 0.1 ppm to 20.0 ppm, or 0.5 ppm to 15.0 ppm, or 1.0 ppm to 10.0 ppm, based on the total weight of the electrolyte.
[0053] In one embodiment of the present invention, the additive is an organic sulfonic acid or salt thereof.
[0054] Typically, nitrogen-containing cationic polymers (NCPs) are the reaction products of amine compounds and epoxide compounds. Suitable amine compounds include, but are not limited to, dialkylamines, trialkylamines, arylalkylamines, diarylamines, imidazoles, triazoles, tetrazoles, benzimidazoles, benzotriazoles, piperidine, morpholines, piperazines, pyridines, oxazoles, benzoxazoles, pyrimidines, quinolines, isoquinolines, and the like. Preferably, the amine compounds include, but are not limited to, diamines of formula (I) or imidazoles of formula (II):
[0055] [ka]
[0056] (In the formula, R 1 , R 2 , R 3 , R 4 are independently H or C1-C3 alkyl; R 5 is H or C1-C6 alkyl; R 6 , R 7 , and R 8 are each independently H or C1-C6 alkyl; R 7 and R 8 may optionally be joined together to form a saturated ring; A is C2-C8 alkylene, C5-C 10 Cycloalkylene, phenylene, and C6-C 20 A is a divalent linking group selected from arylene, A being optionally substituted with C1-C4 alkyl or OH; p, q, and r each independently represent an integer of 0 to 10.
[0057] Examples of diamines of formula (I) include, but are not limited to, ethylenediamine, tetramethyl-1,3-propanediamine, N 1 ,N 4-Diethyl-1,4-butanediamine, Tetramethyl-1,5-pentanediamine, N 1 ,N 6 -dimethyl-1,6-hexanediamine, N,N,N',N'-tetramethyl-1,6-hexanediamine, 1,4-diaminocyclohexane, 1,4-cyclohexane-bis(methylamine), N,N,N',N'-tetramethyl-p-phenylenediamine, p-xylylenediamine, bis[2-(N,N-dimethylamino)ethyl]ether, bis(3-aminopropyl)ethane, 2,2'-[1,2-ethanediylbis(oxy)]bis[N-methylethanamine, 1,1'-[1,2-ethanediylbis(oxy)]bis[2-propanamine], 1,2-bis(3-aminopropoxy)ethane, 3,3'-[oxybis(ethyleneoxy)]bis[N,N-dimethylpropylamine], and 3,3'-[oxybis(propyleneoxy)]bis[N,N-dimethylpropylamine].
[0058] Examples of imidazoles of formula (II) include, but are not limited to, 2H-imidazole, 2-methylimidazole, 4-methylimidazole, 2-ethylimidazole, 2-isopropylimidazole, and 2,5-dimethyl-1H-imidazole.
[0059] Suitable epoxide compounds include those having one epoxide group, diepoxides having two epoxide groups linked together by a bond, or polyepoxides having three or more epoxide groups. Preferably, the epoxide compounds include, but are not limited to, epoxides of formula (III) or diepoxides of formula (IV):
[0060] [ka]
[0061] (In the formula, Y is H or C1-C4 alkyl; X is a halogen; R 9and R 10 are independently H or C1-C4 alkyl; R 11 is C2-C8 alkylene and C5-C 10 is a divalent linking group selected from cycloalkylene; R 11 is optionally substituted with C1-C4 alkyl or OH; where n is an integer from 1 to 20.
[0062] Preferably, in the epoxide of formula (III), X is chlorine or bromine, more preferably chlorine. When Y is a C1-C4 alkyl group, the alkyl group may be unsubstituted or substituted. That is, one or more of its hydrogens may be replaced by another substituent. Examples of compounds of formula (III) include, but are not limited to, epichlorohydrin and epibromohydrin.
[0063] Examples of diepoxides of formula (IV) include, but are not limited to, 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, triethylene glycol diglycidyl ether, 1,3-butanediol diglycidyl ether, glycerol 1,3-diglycidyl ether, neopentyl glycol diglycidyl ether, propylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, poly(propylene glycol) diglycidyl ether, 1,2-cyclohexanedimethanol diglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, poly(ethylene glycol) diglycidyl ether, and poly(polypropylene glycol) diglycidyl ether.
[0064] The preparation of reaction products of amine compounds and epoxide compounds is well known. See, for example, Patent Document 1, Patent Document 2, Patent Document 3, and Patent Document 4. The reaction of the reaction products of the above-mentioned amine compounds and epoxide compounds can be carried out, for example, at a temperature of 30°C to 90°C for 45 minutes to 480 minutes. The reaction products typically have a molar ratio of amine compound to epoxide compound of 10:1 to 1:4, more typically 2:1 to 1:2.
[0065] In one embodiment of the present invention, the additive comprises a nitrogen-containing cationic polymer.
[0066] In one embodiment of the present invention, the nitrogen-containing cationic polymer is the reaction product of a diamine of formula (I) and an epoxide of formula (III):
[0067] [ka]
[0068] (In the formula, R 1 , R 2 , R 3 , and R 4 are independently H or C1-C3 alkyl; A is C2-C8 alkylene, C5-C 10 Cycloalkylene, phenylene, and C6-C 20 A is a divalent linking group selected from arylene, A being optionally substituted with C1-C4 alkyl or OH; Y is H or C1-C4 alkyl; X is a halogen; p, q, and r each independently represent an integer of 0 to 10.
[0069] In another embodiment of the present invention, the nitrogen-containing cationic polymer is the reaction product of a diamine of formula (I) and a diepoxide of formula (IV):
[0070] [ka]
[0071] (In the formula, R 1 , R 2 , R 3 , and R 4 are independently H or C1-C3 alkyl; R 9 and R 10 are independently H or C1-C4 alkyl; R 11 is C2-C8 alkylene and C5-C 10 is a divalent linking group selected from cycloalkylene; R 11 is optionally substituted with C1-C4 alkyl or OH; A is C2-C8 alkylene, C5-C 10 Cycloalkylene, phenylene, and C6-C 20 A is a divalent linking group selected from arylene, A being optionally substituted with C1-C4 alkyl or OH; p, q, and r each independently represent an integer of 0 to 10; where n is an integer from 1 to 20.
[0072] In a further embodiment of the present invention, the nitrogen-containing cationic polymer is the polymerization product of an imidazole of formula (II) with an epoxide of formula (III):
[0073] [ka]
[0074] (In the formula, R 5 is H or C1-C6 alkyl; R 6 , R 7 , and R 8 are each independently H or C1-C6 alkyl; R 7 and R 8 may optionally be joined together to form a saturated ring; Y is H or C1-C4 alkyl; and X is a halogen.
[0075] In yet another embodiment of the present invention, the nitrogen-containing cationic polymer is the polymerization product of an imidazole of formula (II) and a diepoxide of formula (IV):
[0076] [ka]
[0077] (In the formula, R 5 is H or C1-C6 alkyl; R 6 , R 7 , and R 8 are each independently H or C1-C6 alkyl; R 7 and R 8 may optionally be joined together to form a saturated ring; R 9 and R 10 are independently H or C1-C4 alkyl; R 11 is C2-C8 alkylene and C5-C 10 is a divalent linking group selected from cycloalkylene; R 11 is optionally substituted with C1-C4 alkyl or OH; where n is an integer from 1 to 20.
[0078] Typically, the reaction product of the amine compound and the epoxide compound can have a weight average molecular weight (Mw) value in the range of 100 g / mol to 50,000 g / mol, typically 500 g / mol to 30,000 g / mol, and preferably 1,000 g / mol to 10,000 g / mol, although other Mw values may be used.
[0079] In one embodiment of the present invention, the nitrogen-containing cationic polymer has a weight average molecular weight (Mw) of about 1,000 g / mole to about 10,000 g / mole.
[0080] Typically, the amount of the nitrogen-containing cationic polymer in the electrolyte is in the range of 0.1 ppm to 20.0 ppm, or 0.5 ppm to 15.0 ppm, or 1.0 ppm to 10.0 ppm, based on the total weight of the electrolyte.
[0081] In one embodiment of the present invention, the amount of the nitrogen-containing cationic polymer in the electrolyte solution ranges from 0.1 ppm to 20.0 ppm, or from 0.5 ppm to 15.0 ppm, or from 1.0 ppm to 10.0 ppm, based on the total weight of the electrolyte solution.
[0082] The method for producing an electrodeposited copper foil of the present invention can be carried out at a wide range of electrolyte temperatures. The electrolyte temperature is usually about 20°C to about 80°C, preferably about 25°C to about 75°C, and more preferably 30°C to about 70°C.
[0083] The method of manufacturing the electrodeposited copper foil of the present invention can also be carried out by applying a wide range of currents. 2 ~ approx. 100A / dm 2 The deposition can be carried out at a current density in the range of 60A / dm 2 When conducted at higher current densities, the production speed of electrodeposited copper foil can reach at least about 0.25 μm per second, which meets standard industrial production speeds.
[0084] A third aspect of the present invention is to provide a surface-treated electrodeposited copper foil that includes or is made from the electrodeposited copper foil of the present invention.
[0085] Depending on the specific application, there are various types of surface treatments to impart desired properties to the copper foil. To obtain a surface-treated electrodeposited copper foil, the electrodeposited copper foil of the present invention can be subjected to conventional surface treatment steps such as pickling, roughening (e.g., nodule plating), and forming a heat-resistant layer, an oxidation-resistant layer, and / or an adhesion-promoting layer. The surface treatment steps described above can be applied to the matte side, the shiny side, or both sides of the electrodeposited copper foil.
[0086] It is to be noted that none of the above surface treatment processes are expected to reduce the uniformity of the matte surface of the base ED copper foil, i.e., the UF value of the surface treated copper foil of the present invention is expected to be the same as or even lower than the UF value of the base copper foil of the present invention.
[0087] For example, it can be assumed that a surface treatment step such as roughening by electroplating nodules on the matte and / or shiny sides will result in the formation of a nodule layer 4 with a thickness in the range of 100 nm to 1 μm. In addition, nodules plated on the matte side may deposit more in the valleys than on the peaks and vice versa, which may change the average thickness of the ED copper foil after the roughening step.
[0088] Please refer to FIG. 2A, which shows a cross-sectional view of a copper foil according to one embodiment of the present invention. In FIG. 2A, the base foil 1 has a matte surface and a smooth surface, and a number of protrusions are located on the matte surface. The peak height P1 is the distance indicated by the dashed line 2, and the valley height V1 is the distance indicated by the dashed line 3. P1 to P5 refer to the five peak heights on the matte surface, and V1 to V5 refer to the five valley heights on the matte surface. The average thickness (T Ave ) is calculated by adding the average peak height of P1 to P5 and the average valley height of V1 to V5 and dividing the sum by 2. The nodule layer 4 includes a plurality of nodules formed on the shiny surface of the base foil 1.
[0089] 2B, it is noted that when the matte side of the copper foil is roughened according to one embodiment of the present invention, the nodule layer 4 contains a number of nodules that typically form on top of the matte side of the base foil 1. Furthermore, the nodule layer 4 of the matte or shiny side is distinguishable from the base foil 1 by SEM. Thus, the average thickness of the surface treated ED copper foil of the present invention remains the same as the thickness of the untreated base foil 1.
[0090] As mentioned earlier, P.A. 50+The surface area was measured by counting the number of flat-topped protrusions on the matte surface of ED copper foil with a surface area of 50 mm or more after polishing the shiny surface of the foil by about 1 μm. After polishing, the tops of abnormally large and tall protrusions and the nodules precipitated thereon are also flattened. Therefore, the surface area of the matte surface of the roughened copper foil with a surface area of 50 mm or more is 1 μm. 2 Per A max and P.A. 50+ It is expected that the UF value of the ED copper foil of the present invention will be approximately the same after the surface treatment process.
[0091] A fourth aspect of the present invention provides an article comprising or made from the electrodeposited copper foil of the present invention, including a negative electrode current collector for a lithium ion battery, a copper clad laminate, a flexible copper clad laminate, a heat sink, or a printed circuit board.
[0092] Without further elaboration, it is believed that one skilled in the art using the preceding description can utilize the present invention to its fullest extent. Accordingly, the following examples are to be construed as merely illustrative and not limiting of the present invention in any way. EXAMPLES
[0093] The abbreviation "E" stands for "Example" and "CE" stands for "Comparative Example". The Examples and Comparative Examples were prepared in the same manner, except that different electrolytes were used. The performance tests of the Examples and Comparative Examples were also performed in the same or similar manner.
[0094] material Gelatin was purchased from Jellice Pioneer Private Limited Taiwan Branch (Singapore) with model number FL-FCC0.
[0095] Bis(sodium sulfopropyl) disulfide (SPS) was purchased from HOPAX.
[0096] Hydroxyethyl cellulose (HEC) was purchased from DAICEL.
[0097] NCP-A: A compound represented by the formula (I), sold under the trade name Copper Gleam (trademark), T1 by DuPont Electronics, Inc. Wilmington, Del., USA (hereinafter referred to as "DuPont Electronics").
[0098] [ka]
[0099] and a diamine of formula (IV)
[0100] [ka]
[0101] with a diepoxide having a Mw of about 1,000-10,000 g / mol.
[0102] NCP-B: Copper Gleam (trademark), sold by DuPont Electronics under the trade name T2,
[0103] [ka]
[0104] and an imidazole of formula (III)
[0105] [ka]
[0106] with a diepoxide having a Mw of about 1,000-10,000 g / mol.
[0107] NCP-C: sold by DuPont Electronics under the trade name Copper Gleam™, T3,
[0108] [ka]
[0109] with an imidazole of formula (IV)
[0110] [ka]
[0111] with a diepoxide having a Mw of about 1,000-10,000 g / mol.
[0112] Copper sulfate, sulfuric acid, hydrochloric acid, and compounds of unspecified commercial origin were purchased from Sigma-Aldrich Company.
[0113] Preparation of Examples 1 to 13 and Comparative Examples 1 to 7 The ED copper foils of Examples 1 to 13 and Comparative Examples 1 to 7 were produced by the following process.
[0114] First, the electrolyte for each Example or Comparative Example was prepared by thoroughly mixing copper sulfate (260 g / L), sulfuric acid (105 g / L), chloride ions, and additives in the amounts shown in Table 1. Electrodeposition was carried out in an apparatus containing a titanium drum used as the negative electrode (cathode) and a dimensionally stable anode (IrO2 / Ti) used as the positive electrode. A DC power source was used with a current density of 60 A / dm 2 The temperature was set at 50°C. The space between the cathode and anode was filled with the respective electrolyte, and the temperature of the electrolyte was maintained at 60°C. The copper foil of each Example or Comparative Example was directly formed on the surface of a titanium drum for the plating time specified in Table 1. Finally, the copper foil was peeled off from the titanium drum to obtain an electrodeposited copper foil. The copper foil specimens E1 to E13 and CE1 to CE7 were base copper foils, which means that they had not undergone any surface treatment process.
[0115] [Table 1]
[0116] Measurement method The uniformity of the copper foils of Examples 1-13 and Comparative Examples 1-7 was measured, where applicable, by the following method.
[0117] 1. Peak, valley and average thickness (T Ave ) The copper foil obtained in each Example or Comparative Example was cut into test pieces (size: 2 cm x 1 cm) for thickness measurement by SEM. For ease of handling, each test piece was immersed in a room temperature curing epoxy resin to obtain a transparent epoxy-coated Cu foil test piece. Note that the epoxy coating of the copper foil test piece was not visible or detectable by SEM.
[0118] To obtain high quality electron channeling contrast images, a scanning electron microscope (models: JEOL IT300HR, IT800SHL) was set to backscattered electron detector, contrast enhancement, reduced brightness, and scan speeds of over 40 seconds. Five different peaks and five different valleys heights for each foil sample were recorded and averaged in Tables 2-1 and 2-2 below. The average thickness (T Ave ) is calculated by summing the averaged peak height and the averaged valley height and then dividing by two, and is also given in Table 2-2.
[0119] [Table 2]
[0120] [Table 3]
[0121] 2. The maximum surface area of the protrusions that have a flattened surface after polishing (A max ), and 50 μm on a matte surface with a flattened surface after polishing 2 The number of protrusions with a surface area of at least 50+ ) A copper foil specimen of each Example or Comparative Example was cut into a 10 cm x 10 cm square. The specimen was then placed on a glass plate with the matte side down in contact with the glass plate. The shiny side of the specimen was polished using Buehler SiC sandpaper, #P1200. After polishing the shiny surface by about 1 μm, the flattened tops of the taller / larger protrusions were revealed on the matte side of the specimen. Photographs of the matte side of each specimen were taken with an optical microscope (OLYMPUS STM7-CS100) equipped with a 5x objective lens and a 10x eyepiece. The observation area of each photograph was 5,892,250 μm. 2 It was.
[0122] The photographs of each copper foil specimen were analyzed by software to measure the surface area of each protrusion with a flattened top, and the surface area in the photograph was determined to be 50 μm 2 Number of flattened apexes (PA 50+ For ease of comparison, the area of the observation mat surface was 5,892,250 μm 2 Divide the number of protrusions counted above by 5.892 to get the number of protrusions per 1 mm of matte surface. 2 (i.e. 1,000,000μm 2 ) per PA 50+ obtained.
[0123] As mentioned above, the uniformity factor (UF) of the matte surface of each of the examples and comparative examples is calculated as follows: UF=A max / T Ave (Formula 1) (In the formula, A max : the maximum surface area of the protrusions on the matte surface with flattened tops after polishing; and T Ave : Average thickness of ED copper foil (T Ave )).
[0124] The measured and calculated data for each copper foil specimen are shown in Table 3.
[0125] [Table 4]
[0126] As shown in Tables 1 to 3, the electrodeposited copper foils of the present invention in Examples 1 to 13 each had a UF value of 5.5 μm or less and a matte surface thickness of 1 mm 2 Around PA 50+ The matte surface of the ED copper foils E1 to E13 having thicknesses ranging from about 69 μm to about 374 μm was improved significantly by adding nitrogen-containing cationic polymers including NCP-A, NCP-B, and / or NCP-C to the electrolyte, regardless of the presence of gelatin or HEC.
[0127] In contrast, Comparative Examples 1-7 and the resulting copper foils, which were made using only the nitrogen-containing cationic polymer in their respective electrolytes and similar amounts of conventional additives such as gelatin and / or HEC, exhibited poor uniformity as judged by their respective UF values (i.e., greater than 5.5 μm). In addition, the matte side of each of the copper foil specimens CE1-7 had a thickness of 1 mm2 of the matte side ranging from 9.0 to 25.6. 2 Around PA 50+ had the following characteristics:
[0128] FIG. 3A shows that the matte surface has poor uniformity, with a UF of 7.85 μm and a matte surface of 1 mm 2 Around PA 50+ FIG. 3B shows an SEM cross-sectional image of a copper foil specimen of CE3, which had a matte surface uniformity, a UF of 1.65 μm, and a matte surface 1 mm thick. 2 Around PA 50+ 4 shows an SEM cross-sectional image of an E9 copper foil specimen, which had a thermal expansion coefficient of 1.7.
[0129] Therefore, the method of the present invention effectively suppresses the growth of abnormally tall and large protrusions on the matte surface of ED copper foil during electrodeposition when the thickness of the copper foil is about 30 μm to about 400 μm. PCBs manufactured from copper clad laminates or flexible copper clad laminates containing the ED copper foil of the present invention are expected to have improved safety and reliability, and fewer etching defects and / or short circuit problems.
[0130] While specific embodiments of the present invention have been shown and described, additional modifications and improvements will occur to those skilled in the art. It is understood, therefore, that the invention is not limited to the specific forms shown, and it is intended that the appended claims cover all modifications that do not depart from the spirit and scope of the invention. [Explanation of symbols]
[0131] 1 Base foil 2 Dashed Line 3. Dashed Line 4 Nodule layer P1~P5 Top height V1~V5 Valley height
Claims
1. Average thickness (T Ave ) An electrodeposited copper foil having a matte surface and a glossy surface, the matte surface of the electrodeposited copper foil includes a plurality of protrusions; After polishing, the matte surface is 1 mm 2 50 μm per 2 The number of protrusions on the mat surface having a flattened top with a surface area of at least 50+ ) is 8.0 or less; The average thickness is measured by scanning electron microscopy (SEM); the tops of the protrusions on the matte side are planarized by a) placing the electrodeposited copper foil on the glass substrate such that the matte side is in contact with the glass substrate; and b) polishing approximately 1 μm of the shiny side of the electrodeposited copper foil using 1200 grit silicon carbide sandpaper; The number and surface area of the protrusions of the matte surface having flattened tops after polishing are counted and measured using an optical microscope having a magnification of 50 times or greater and a resolution of at least 0.1 μm.
2. The matte surface of the electrodeposited copper foil is 2 PA of 6.0 or less 50+ The electrodeposited copper foil of claim 1 , having
3. The matte surface of the electrodeposited copper foil has a uniformity factor (UF) of 5.5 μm or less, and the UF is expressed by the following formula 1: UF = A max / T Ave (Equation 1) is calculated according to In the formula, A max is the maximum surface area (A) of the protrusions of the matte surface having a flattened top after polishing max ) and T Ave is the average thickness of the electrodeposited copper foil; The electrodeposited copper foil according to claim 1.
4. 2. The electrodeposited copper foil of claim 1, wherein the matte side of the electrodeposited copper foil has a UF of 4.0 μm or less.
5. A method for producing the electrodeposited copper foil according to claim 1, i) providing an electrolyte in an electrolytic cell; ii) applying a current at a current density to an anode plate and a rotating cathode drum spaced apart from each other in the electrolyte; iii) electrodepositing copper foil onto the rotating cathode drum; and iv) peeling off the copper foil formed in step iii) to obtain an electrodeposited copper foil; Including, the electrodeposited copper foil having an average thickness of about 30 μm to about 400 μm; The electrodeposition in step iii) is at about 30 A / dm 2 ~ approx. 100 A / dm 2 at a current density of; The electrolyte solution is about 120 g / L to about 450 g / L of copper sulfate; about 30 g / L to about 140 g / L of sulfuric acid; about 0.1 ppm to about 60 ppm chloride ions; and About 0.1 ppm to about 50 ppm of additive A method comprising:
6. 6. The method of claim 5, wherein the electrodeposition in step iii) is carried out at a temperature of the electrolyte from about 20° C. to about 80° C.
7. The method of claim 5 , wherein the additive in the electrolyte solution comprises gelatin, glue, cellulose, an organic sulfonic acid or its salt, a nitrogen-containing cationic polymer, or a mixture thereof.
8. The method of claim 7, wherein the additive comprises a nitrogen-containing cationic polymer, the nitrogen-containing cationic polymer having a weight average molecular weight of about 1,000 to about 10,000 g / mole.
9. 9. The method of claim 8, wherein the nitrogen-containing cationic polymer is a reaction product of a diamine of formula (I) or an imidazole of formula (II) with an epoxide of formula (III) or a diepoxide of formula (IV): 【Chemistry 1】 (In the formula, R 1 , R 2 , R 3 , and R 4 are independently H or C 1 ~C 3 is alkyl; R 5 is H or C 1 ~C 6 is alkyl; R 6 , R 7 , R 8 Each of is independently H or C 1 ~C 6 alkyl, R 7 and R 8 may optionally be joined together to form a saturated ring; R 9 and R 10 are independently H or C 1 ~C 4 is alkyl; R 11 is C 2 ~C 8 Alkylene and C 5 ~C 10 is a divalent linking group selected from cycloalkylene; R 11 is optionally C 1 ~C 4 may be substituted with alkyl or OH; A is C 2 ~C 8 Alkylene, C 5 ~C 10 Cycloalkylene, phenylene, and C 6 ~C 20 A is a divalent linking group selected from arylene, and A is optionally C 1 ~C 4 may be substituted with alkyl or OH; Y is H or C 1 ~C 4 is alkyl; X is a halogen; p, q, and r each independently represent an integer from 0 to 10; and n is an integer from 1 to 20.
10. 10. A surface treated electrodeposited copper foil comprising the electrodeposited copper foil of claim 1, wherein one surface of the electrodeposited copper foil has been subjected to at least one surface treatment step.
11. The surface-treated electrodeposited copper foil according to claim 10, wherein the surface treatment step includes an acid-washing step, a roughening step, a heat-resistant layer forming step, an oxidation prevention layer forming step, or an adhesion promotion layer forming step.
12. 11. An article comprising the electrodeposited copper foil of claim 1 or the surface-treated electrodeposited copper foil of claim 10.
13. 13. The article of claim 12, which is a negative electrode current collector for a lithium ion battery, a copper clad laminate, a flexible copper clad laminate, a heat sink, or a printed circuit board.
Citation Information
Patent Citations
Copper plating bath and plating method for substrate using the copper plating bath
US6800188B2
Plating method
US7374652B2
Leveler compounds
US7662981B2
Plating bath and method
US8268158B2